The Role of Intellectual Capital in Improving Micro, Small, And Medium-Scale Business Performance in The Hostel And Culinary Sector in Pekanbaru, Indonesia - Astri Ayu Purwati; Budiyanto Budiyanto; Suhermin Suhermin (Yayasan Riset dan Pengembangan Intelektual, 2021)
The increased level of competitiveness and Micro, Small, and Medium-Scale Business (MSME) performance in the hostel and culinary sector in Indonesia, especially in Pekanbaru, need more concerns since MSME is an important business sector to encourage the economy of a country and reduce the unemployment rate by creating job opportunities. In the technology era, the development of the intellectual capital concept suitable for MSME is needed due to the current competitive and disruptive business area. This study was conducted in 378 MSMEs in the hostel and culinary sector in Pekanbaru city. The data analysis technique in this study was Structural Equation Modeling (SEM) assisted by AMOS. The result of this study showed that human capital influenced the financial performance and non-financial performance of MSME in the hostel and culinary sector in Pekanbaru City, while technology capital did not influence the non-financial performance of MSME in the hostel and culinary sector in Pekanbaru city. Customer capital influenced the financial and non-financial performances of MSME in the hostel and culinary sector in Pekanbaru city. Social capital influenced the financial and non-financial performances of MSME in the hostel and culinary sector in Pekanbaru city. Non-financial performance influenced the financial performance of MSME in the hostel and culinary sector in Pekanbaru city.